Emotional outcomes of regulation strategies used during personal music listening: A mobile experience sampling study. (September 2014) - Randall, William M.; Rickard, Nikki S.; Vella-Brodrick, Dianne A.
Music is frequently used to support emotional health and well-being, with emotion regulation the most commonly reported mechanism. Music-based emotion regulation has not yet been extensively investigated within the broader emotion regulation framework. The effects of music-based emotion regulation on emotional state and well-being outcomes have also rarely been tested in real time. The current study aimed to determine the consequences of emotion regulation strategies used during music listening, in terms of hedonic outcomes, and associations with emotional health and well-being. A sample of 327 participants used the MuPsych application (app), a mobile experience sampling methodology designed for the real-time and ecologically-valid measurement of personal music listening. Results revealed that using music to regulate a recently experienced emotion (response-focused strategies) yielded the greatest hedonic success, but was associated with poorer emotional health and well-being. Music-based emotion regulation differed from non-music emotion regulation findings in several key ways, suggesting that music-based emotion regulation does not occur in accordance with the process model. This supported the notion that personal music listening is utilized as an independent regulatory resource, allowing listeners to reach specific emotional goals. Regulation strategies are selected to reach a desired hedonic outcome, based on initial mood, and influenced by emotional health and well-being.